2017
DOI: 10.1089/neu.2016.4670
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Peripheral Vision Reaction Time Identifies White Matter Disruption in Patients with Mild Traumatic Brain Injury

Abstract: This study examined whether peripheral vision reaction time (PVRT) in patients with mild traumatic brain injury (mTBI) correlated with white matter abnormalities in centroaxial structures and impairments in neuropsychological testing. Within 24 h after mTBI, crossed reaction times (CRT), uncrossed reaction times (URT), and crossed-uncrossed difference (CUD) were measured in 23 patients using a laptop computer that displayed visual stimuli predominantly to either the left or the right visual field of the retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…These findings were also supported by a study of adults who were at 1-year post-concussion (Hellstrøm et al, 2017). Similarly, altered diffusivity acutely after the concussion is associated with decreased verbal memory and executive functioning, and increased reaction time at 1-year post-injury (Geary et al, 2010;Womack et al, 2017). These studies suggest that microstructural alterations may underlie the cognitive and behavioral problems that present following concussion, but further research is needed to determine if these associations still hold true in children and adolescents long after injury.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…These findings were also supported by a study of adults who were at 1-year post-concussion (Hellstrøm et al, 2017). Similarly, altered diffusivity acutely after the concussion is associated with decreased verbal memory and executive functioning, and increased reaction time at 1-year post-injury (Geary et al, 2010;Womack et al, 2017). These studies suggest that microstructural alterations may underlie the cognitive and behavioral problems that present following concussion, but further research is needed to determine if these associations still hold true in children and adolescents long after injury.…”
Section: Introductionmentioning
confidence: 57%
“…Acutely following concussion, clinical or behavioral manifestations of white matter alterations may include worse post-concussion symptom severity and poorer cognitive performance (Geary, Kraus, Pliskin, & Little, 2010;Hellstrøm et al, 2017;Khong, Odenwald, Hashim, & Cusimano, 2016;Womack et al, 2017). A systematic review conducted by Khong and colleagues concluded that decreased FA and increased MD and RD are correlated with greater symptom severity and prolonged post-concussion symptoms (Khong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The microstructure differentiating high and low reaction time was not perceptible visually as demonstrated in Fig 1, motivating the use of TBM 13,[26][27][28] to discover the complex pattern. Our 3D-TBM technique 13 is an image-transformation framework that fa- cilitates the discovery of this pattern through analysis in a transform domain.…”
Section: Analyzing Fa Spatial Distribution Using Transport-based Morpmentioning
confidence: 99%
“…Our 3D-TBM technique 13 is an image-transformation framework that fa- cilitates the discovery of this pattern through analysis in a transform domain. [26][27][28] On-line Fig 1 illustrates the system diagram in the On-line Appendix. The interested reader is referred to Kundu et al 13 for the mathematic derivation of 3D-TBM.…”
Section: Analyzing Fa Spatial Distribution Using Transport-based Morpmentioning
confidence: 99%
See 1 more Smart Citation